IMPACT OF POST-BREEDING HORMONAL TREATMENT ON CONCEPTION IN REPEAT BREEDING GIR CATTLE AT A GAUSHALA - PARMAR, S V; PATEL, J A; DHAMI, A J; SHAH, R G (The Indian Journal of Animal Reproduction, 2016)
Repeat breeding Gir cattle (n=24) of a Gaushala were randomly and equally allotted to buserelin group (postbreeding 0.02 mg buserelin acetate, i.m.), hCG group (post-breeding 1500 IU hCG, i.m.), progesterone group (Day 6post-breeding 500 mg hydroxyl progesterone caproate, i.m.) and control (no hormonal treatment). The overall conceptionrate (till cycle II post-treatment) of hormonal treatment groups was higher compared to controls (72.2 vs 33.3%,p0.05) between treatment groupsas well as between conceived and non-conceived counterparts. This study indicated beneficial role of the use ofhormone therapy for improving conception rate in repeat breeding Gir cattle at Gaushalas.
Keywords: Gaushala; Gir; hCG; Progesterone; Repeat breeding